[6 + 3] Annulations of Morita–Baylis–Hillman carbonates and dicyanoheptafulvene. Issue 45 (4th November 2021) - Jia, Ruo-Ling; Liu, Qing-Ling; Yang, Long-Wei; Deng, Shi; Song, Yang
Abstract : A [6 + 3] annulation reaction of Morita–Baylis–Hillman carbonates and dicyanoheptafulvene is accomplished by employing commercially available triphenylphosphine as the Lewis base catalyst. Abstract : A [6 + 3] annulation reaction of Morita–Baylis–Hillman carbonates and dicyanoheptafulvene is accomplished by employing commercially available triphenylphosphine as the Lewis base catalyst. A spectrum of densely functionalized bicyclo[4.3.1]decane architectures are efficiently constructed with exclusive diastereoselectivity and good yield (up to 95%).